Ceramics manufacturing method

The ceramic manufacturing method addresses the limitations of existing methods by applying mechanochemical treatment and sintering to enhance the high temperature strength and durability of ceramics, while reducing binder usage and alkaline residue.

JP7671648B2Active Publication Date: 2025-05-02MITSUBISHI HEAVY IND LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021123584
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-07-28
Publication Date
2025-05-02
Estimated Expiration
2041-07-28

AI Technical Summary

Technical Problem

Existing ceramic manufacturing methods require high amounts of organic binders and lengthy degreasing processes, which can lead to cracking and limitations in high temperature strength due to residual alkaline components.

Method used

A method involving mechanochemical treatment of ceramic particles, mixing with a ceramic sol, solidification, and subsequent sintering to produce ceramics with enhanced high temperature strength and durability, while minimizing the use of binders.

Benefits of technology

The method efficiently produces ceramics with high temperature strength and durability by increasing the hardness of the molded body and maintaining strength during sintering, thus reducing the need for lengthy degreasing processes and minimizing alkaline residue.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007671648000001
    Figure 0007671648000001
  • Figure 0007671648000002
    Figure 0007671648000002
Patent Text Reader

Abstract

To provide a method for producing ceramic excellent in high temperature strength and durability and moldable in such a manner that the amount of use of an organic binder is reduced.SOLUTION: Raw material powder comprising mechanochemical-treated ceramic powder and a ceramic sol are mixed and molded, and the same is solidified by sol polymerization reaction at a room temperature to produce a molded body, followed by sintering.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to methods for making ceramics. [Background technology]

[0002] Ceramics are sometimes used for components that require high-temperature strength and durability, such as firebricks, crucibles, exhaust gas filters, and SOFC substrates. Ceramics are produced by forming them using metal molds, injection molding, or 3D modeling, and then sintering them. Because forming requires a large amount of organic binder (resin), a long degreasing process is necessary. In addition, cracks often occur during degreasing. In recent years, technology has been developed to solidify ceramics without going through such a process.

[0003] Patent Document 1 describes a method for producing a non-calcined silica solidified body, which comprises a granulation and compression step in which silica particle raw material contained in an alkaline solution having an alkali concentration of 1 M to 5 M is granulated and uniaxially compressed to form a first solid body, a curing step in which the first solid body is cured to crosslink the silica particles to form a second solid body, and a drying step in which the second solid body is dried. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2019-196279 A Summary of the Invention [Problem to be solved by the invention]

[0005] By producing an uncalcined solidified silica body using the method described in Patent Document 1, it is possible to produce a binder-free solidified silica body without sintering. However, the uncalcined solidified silica body is formed using a strong alkaline solution with a high alkali concentration, and then dried and solidified. Therefore, the alkaline solution that can be used is limited, and the alkaline components remain in the produced uncalcined solidified silica body, which deteriorates its high-temperature strength.

[0006] The present disclosure has been made in consideration of the above circumstances, and aims to provide a method for producing ceramics that uses as little binder as possible and efficiently produces ceramics that have high high-temperature strength and durability. [Means for solving the problem]

[0007] In order to solve the above-mentioned problems and achieve the objectives, the present disclosure provides a method for manufacturing ceramics, comprising the steps of performing mechanochemical treatment on ceramic particles, producing a mixture by mixing the mechanochemically treated ceramic particles with a ceramic sol, pouring the mixture into a mold, solidifying the mixture to produce a molded body, and removing the molded body from the mold and sintering it. Effect of the Invention

[0008] According to the present disclosure, ceramics having high high-temperature strength and durability can be efficiently produced. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a flowchart showing an example of a method for producing ceramics according to this embodiment. [Diagram 2] FIG. 2 is a schematic diagram showing the bonds between ceramic particles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present disclosure will be described in detail below with reference to the drawings. Note that the present disclosure is not limited to the following description. In addition, the components in the following description include those that a person skilled in the art can easily imagine, those that are substantially the same, and those that are within the so-called equivalent range.

[0011] FIG. 1 is a flow chart showing an example of a method for manufacturing a ceramic molded body according to the present embodiment. In the process shown in FIG. 1, an operator executes each step using various devices. Here, ceramics are produced by solidifying inorganic ceramics to generate a molded body, and sintering it. Ceramics can be used as various structures produced using a mold, and can be used, for example, for firebricks, crucibles, exhaust gas filters, SOFC substrates, artificial teeth, precision casting molds, cores, etc.

[0012] First, mechanochemical treatment is performed on ceramic particles (step S12). Examples of ceramic particles include silica (SiO2), alumina (Al2O3), titania (TiO2), zirconia (ZrO2), yttria (Y2O3), and composite oxides thereof. Examples of particle diameters of ceramic particles are 0.1 μm or more and 100 μm or less. The particle diameters of ceramic particles can be measured and calculated using a laser diffraction scattering method or the like.

[0013] Mechanochemical treatment is a process that destabilizes and chemically activates the bonds on the surface of ceramic particles. vinegar The mechanochemical treatment can be carried out by rotating a container containing balls having a larger particle size and higher rigidity than the particles in a ball mill for a predetermined period of time. Examples of the balls include balls made of alumina or zirconia and having a diameter of 1 mm to 20 mm. In the mechanochemical treatment, it is preferable to place multiple balls inside the container. It is also preferable to use balls with different diameters, for example, balls with a diameter of φ10 mm and balls with a diameter of φ15 mm. An example of the container is a bottle-shaped container made of plastic. In the mechanochemical treatment, it is preferable to mix in a dry ball mill for 0.5 hours to 50 hours.

[0014] Next, the mechanochemically treated ceramic particles and the ceramic sol are mixed (step S14). The ceramic sol is a ceramic sol in which ceramic particles are dispersed in a solvent. Examples of the ceramic particles dispersed in the sol include silica (SiO2), alumina (Al2O3), titania (TiO2), zirconia (ZrO2), yttria (Y2O3), and composite oxides thereof, and silica (SiO2), alumina (Al2O3), and composite oxides thereof are preferred. The ceramic particles have a particle size of 5 nm or more and 100 nm or less. In addition, water, alcohol, methyl ethyl ketone, and the like can be used as the solvent. The ceramic sol preferably has a pH of 9 or more and 11 or less. The mixing ratio of the ceramic particles and the ceramic sol is preferably 10 wt% or more and 80 wt% or less by weight of the solid content in the ceramic particles and the ceramic sol. The process of mixing the mechanochemically treated ceramic particles and the ceramic sol is carried out by putting the mechanochemically treated ceramic particles and the ceramic sol into a mixing device such as a ball mill and mixing them by stirring for, for example, one hour to produce a mixture. The mixture may contain ceramic particles that have not been mechanochemically treated.

[0015] Next, the mixture is poured into a mold (step S16). The mixture of ceramic particles and ceramic sol is poured into a mold having a shape to be manufactured, and the mixture fills the inside of the mold.

[0016] Next, the mixture inside the mold is solidified to produce a molded body (step S18). The solidification process is a process of drying the mixture by storing it in a dryer at a temperature of 20° C. to 100° C. and a humidity of 10% to 80% for 0.5 hours to 168 hours.

[0017] FIG. 2 is a schematic diagram showing the bonding between ceramic particles. In the mixture, ceramic particles 14 of the ceramic sol are arranged between ceramic particles 12 that have been subjected to mechanochemical treatment. FIG. 2 shows a case where the ceramic particles 12, ceramic particles, and dissolved ceramic molecules 14 are silica. As shown in FIG. 2, by subjecting the ceramic particles 12 to mechanochemical treatment, OH groups are easily formed on the surfaces inside the mixture. OH groups are also present on the surfaces of the ceramic particles and the dissolved ceramic 14. By performing a solidification treatment in this state, a dehydration polymerization reaction occurs, and the ceramic particles 12 are bonded together at bonding parts 16 including the ceramic particles. The solidified molded body has a predetermined strength because the ceramic particles 14 are bonded together at bonding parts 16.

[0018] Next, the solidified green body is removed from the mold (step S20). Since the green body has a predetermined strength or more due to the solidification process, the green body maintains its shape even after being removed from the mold.

[0019] Next, the compact is sintered to produce a ceramic sintered body (step S22). Here, the sintering process is a process in which the solidified body is placed in a sintering furnace and heated at 900° C. to 1700° C. for 0.5 hours to 100 hours.

[0020] The method for producing ceramics involves mechanochemically treating ceramic particles, mixing the mechanochemically treated ceramic particles with a ceramic sol to produce a mixture, molding the mixture and solidifying it to produce a molded body, and sintering the molded body to produce ceramics. In this way, by subjecting the ceramic particles to mechanochemical treatment, it is possible to increase the hardness of the molded body produced by the solidification process in which the mixture is solidified at room temperature. Furthermore, by sintering the molded body, it is possible to produce a ceramic molded body with high strength. It is also possible to minimize the amount of binder used, or to use no binder at all, to produce a ceramic. t Ceramic sol containing fine particles of ceramic vinegarBy maintaining the bonds between particles, long debinding periods are not necessary, shortening the process time and preventing cracks during sintering.

[0021] Moreover, the strength of the molded body can be increased by sintering the molded body. Therefore, the molded body only needs to be able to be handled and have a strength that is not damaged during the sintering process. For this, a ceramic sol having a pH of 9 to 11 is sufficient, and a more highly alkaline solvent is not required. Furthermore, since the alkali concentration of the molded body and sintered body can be prevented from becoming too high, a decrease in high-temperature strength can be prevented.

[0022] Next, an example of a method for producing ceramics will be described. In the example, as a mechanochemical treatment, zirconia balls of Φ15 mm and Φ10 mm and ceramic particles were put into a 500 ml plastic container, and a dry ball mill was carried out for three days. In addition, ceramic particles and ceramic sol were put into the ball mill and mixed for 1 hour to produce a mixture. After that, a 100 ml plastic container was used as a mold, and the mixture was poured into the plastic container. With the mixture poured into the plastic container, it was dried in a dryer at 40°C and a humidity of about 20% for one day as a solidification treatment.

[0023] In this example, the porosity and hardness of the dried molded body were measured. In addition, the dried molded body was heat-treated at 900°C for 4 hours as a sintering process to produce a ceramic sintered body, and the porosity and hardness were measured. The porosity was measured by the Archimedes method. The hardness was measured using a Vickers hardness tester.

[0024] In Example 1, silica with a particle size of 0.6 μm (SFP-30M manufactured by Denka) was used as the ceramic particles. In the mechanochemical treatment, 50 g of silica was added. In addition, Nissan Chemical's silica sol "ST30" (solid content 30 wt%, pH 10) was used as the ceramic sol. The weight ratio of the ceramic particles to the ceramic sol in the mixture was ceramic particles:ceramic sol=30:70 (solid content 51 wt%). In addition, as Comparative Example 1, a molded body and a sintered body were also evaluated, which were produced by the same treatment except that silica not subjected to the mechanochemical treatment was used.

[0025] The hardness (HV5) of the green body (body after solidification and before sintering) of Example 1 was 149.9, and the porosity was 14.1%. The hardness (HV5) of the sintered body (body after sintering) of Example 1 was 265, and the porosity was 13.4%. The hardness (HV5) of the green body (body after solidification and before sintering) of Comparative Example 1 was 87.7, and the porosity was 36.3%. The hardness (HV5) of the sintered body (body after sintering) of Comparative Example 1 was 231.5, and the porosity was 14.6%.

[0026] In Example 2, alumina with a particle size of 0.2 μm (AKP-53 manufactured by Sumitomo Chemical) was used as the ceramic particles. In the mechanochemical treatment, 50 g of silica was added. Furthermore, a silica sol "ST30" manufactured by Nissan Chemical (solid content 30 wt%, pH 10) was used as the ceramic sol. The weight ratio of the ceramic particles to the ceramic sol in the mixture was ceramic particles:ceramic sol=60:40 (solid content 72 wt%). Furthermore, as Comparative Example 2, evaluation was also performed on a molded body and a sintered body produced by the same treatment except that alumina not subjected to mechanochemical treatment was used. In Example 2 and Comparative Example 2, hardness was evaluated.

[0027] The hardness (HV5) of the green body (body after solidification and before sintering) of Example 2 was 54.9. The hardness (HV5) of the sintered body (body after sintering) of Example 2 was 141. The hardness (HV5) of the green body (body after solidification and before sintering) of Comparative Example 2 was 39.0. The hardness (HV5) of the sintered body (body after sintering) of Comparative Example 2 was 136.

[0028] As described above, it can be seen that the strength of the molded body is increased by performing mechanochemical treatment, regardless of whether silica or alumina is used as the ceramic particles. In particular, when silica is used, the hardness of the molded body is about three times that of the comparative example, making it easier to prevent the molded body from being damaged or deformed when it is removed from the mold or placed in a sintering furnace. In addition, the hardness after sintering also tends to be higher in the examples.

[0029] Next, as Example 3, mechanochemically treated ceramic vinegar The mixture of the particles and the ceramic sol was mixed with non-mechanochemically treated ceramic particles to produce a ceramic molded body, and the hardness was evaluated. vinegar The particles used were silica similar to those in Example 1. Example 3 was a mechanochemically treated ceramic. vinegar 50g of particulate silica and non-mechanically treated ceramic vinegar A mixture was prepared by mixing 450 g of alumina particles having a particle size of 20 μm and 150 g of silica sol (ST30, pH 10, manufactured by Nissan Chemical Industries, Ltd.) as a ceramic sol. In Example 3, the mixture was treated in the same manner as in Example 1 to prepare a molded body. In Comparative Example 3, instead of the mechanochemically treated ceramic particles, non-mechanochemically treated ceramic particles were used. vinegar particle and A compact was made from the mixture to which silica was added.

[0030] The hardness of the solidified bodies was measured. The hardness was measured using a Vickers hardness tester. The hardness (HV1) of the molded body of Example 3 was 19.0, and the hardness (HV1) of the molded body of Comparative Example 3 was 8.5. From the above, it can be seen that even when non-mechanochemically treated ceramic particles are used in the mixture, the hardness of the molded body is improved by including mechanochemically treated ceramic particles in the mixture. It can be seen that the hardness is improved even when the amount of non-mechanochemically treated ceramic particles is greater than the amount of mechanochemically treated ceramic particles, as in Example 3.

[0031] Next, in Example 4, the pH of the silica sol was set to 8, 9, 10, and 10.5, and the hardness of the molded body was evaluated. In Example 4, NH3 or HNO3 was added to the mixture of Example 3 to adjust the pH of the mixture (slurry). Molded bodies were made for each mixture, and the hardness was evaluated.

[0032] As a result of the evaluation, when the pH was 8, the hardness (HV1) was 10.0, when the pH was 9, the hardness (HV1) was 14.9, when the pH was 10, the hardness (HV1) was 19.0, and when the pH was 10.5, the hardness (HV1) was 19.5. Furthermore, when the pH was higher than 11, the amount of alkaline components in the compact increased, and the high-temperature strength decreased. From the above, by setting the pH at 9 or more and 11 or less, it is possible to increase the strength of the compact and also the high-temperature strength of the sintered body. [Explanation of symbols]

[0033] 12 Ceramic particles 14 Microparticles and molecules contained in ceramic sol 16 Joint

Claims

1. performing a mechanochemical treatment on the ceramic particles; A step of producing a mixture by mixing the ceramic particles subjected to the mechanochemical treatment with a ceramic sol; pouring the mixture into a mold; solidifying the mixture to produce a compact; and removing the compact from the mold and sintering; the ceramic particles are any one of silica (SiO 2 ), alumina (Al 2 O 3 ), titania (TiO 2 ), zirconia (ZrO 2 ), yttria (Y 2 O 3 ), and composite oxides of silica (SiO 2 ), alumina (Al 2 O 3 ), titania (TiO 2 ), zirconia (ZrO 2 ), and yttria (Y 2 O 3 ); The ceramic sol is any one of silica (SiO 2 ), alumina (Al 2 O 3 ), titania (TiO 2 ), zirconia (ZrO 2 ), yttria (Y 2 O 3 ), and a composite oxide of silica (SiO 2 ), alumina (Al 2 O 3 ), titania (TiO 2 ), zirconia (ZrO 2 ), and yttria (Y 2 O 3 ); The ceramic sol has a pH of 9 or more and 11 or less. A method for manufacturing ceramics.

2. The method for producing ceramics according to claim 1, wherein the ceramic particles are at least one of silica and alumina.

3. 3. The method for producing ceramics according to claim 1, wherein the ceramic sol contains at least one of silica and alumina.

4. The method for producing ceramics according to claim 1 , wherein the mixture contains ceramic particles that have not been mechanochemically treated.

5. 5. The method for producing ceramics according to claim 1, wherein the step of producing the molded body comprises holding the mixture poured into the mold at 20° C. or more and 100° C. or less for 0.5 hr or more and 168 hr or less to produce the molded body.

6. The method for producing ceramics according to claim 1 , wherein the step of performing the mechanochemical treatment comprises performing the mechanochemical treatment for 0.5 hours or more and 50 hours or less.

Citation Information

Patent Citations

  • Aluminous ceramic filter and production thereof

    JP1991127615A

  • Printed matter with photocatalyst and its continuous manufacturing method

    JP2008120055A

  • Sodium hexatitanate and method for producing the same

    JP2008303121A

  • Method for solidifying ceramic powder

    JP2009203101A

  • Porous aluminum titanate, sintered compact thereof and method for producing the porous aluminum titanate

    JP2009263182A